A tailored within-community specimen collection strategy increased uptake of cervical cancer screening in a cross-sectional study in Ghana - Adolf K. Awua; Edwin K. Wiredu; Edwin A. Afari; Ahmad S. Tijani; Gabriel Djanmah; Richard M. K. Adanu (BMC, 2017)
Abstract Background The implementation of cervical cancer screening strategies has reported different rates of success in different countries due to population specific factors that limit women's participation. We report observations and the development of a community-based specimen collection strategy which resulted from interactions with women in the study communities, following an initial low response to a hospital based cervical cancer screening strategy. Method Women were recruited by a house survey and invited to report at a hospital either within a week or after a week for self and health-personnel specimen collections. However, due to the very low response and subsequent interactions with the women of the communities, another strategy was developed that required recruited women report at a central location within their respective communities for specimen collections at times that did not interfere with their daily routines. Results For specimen collection, of the 156 participants who opted to report after a week at the hospital, 60 (38.5%) reported. Of the 118 participants who opted to report within 1 week at the hospital, 55 (46.6%) reported. Of the 103 participants were invited to report at a specified location within the community, 98 (95.1%) reported. An overall response rate of 60.4% was attained. Almost 89.7% (226 of 253) of the women performed both self and health personnel sample collection. Conclusion The community-based strategy with self-specimen collection and HPV testing holds great potential for increasing women's participation in cervical cancer screening in Ghana as compared to the hospital based strategy.